Effects of the application techniques of self-adhesive resin cements on the interfacial integrity and bond strength of fiber posts to dentin (Journal of Applied Oral Science, 2016)
Objective: To evaluate the influence of an application technique of a glass-fiber post using self-adhesive resin cements on the push-out bond strength and the presence of bubbles in the root thirds. The cements were either applied according to the manufacturer's instruction or using a commercial delivering system (Centrix), at which the cement pastes were collected and applied after manipulation. Material and Methods: Self-adhesive resin cements (RelyX U200/3M ESPE-U200; Maxcem Elite/Kerr-MAX; Clearfil SA Cement/Kuraray-CSA) and a conventional cement (RelyX ARC/3M ESPE-ARC) were used to cement a post and applied either based on the manufacturer's instructions or using a Centrix syringe to deliver the cements directly onto the post of choice, or directly into canal. The roots were scanned with a micro-computed tomography (μCT) and then sectioned into nine 1-mm thick slices for a push-out bond strength test. The μCT images showed the percentage of bubbles in the root thirds (cervical, medium, and apical). Data were analyzed with three-way ANOVA/Tukey (α=0.05). Results: Triple interaction was not significant (p>;0.05). The interaction “material” vs “root third” was not significant. A significant interaction was observed between “material” vs “application technique” (p;0.05). Significantly higher bond strength was observed when the self-adhesive resin cements were applied using the Centrix delivery system, in comparison with the manufacturer's instructions (p;medium>;apical (p